Didactic Strategy Proposal for Initial Research Training - E.M. Robaina Aguirre; M. Valdes Pedroso (Editura Universitatii Transilvania din Brasov, 2023)
The objective of this research is to propose a didactic strategy for the investigative training process of the students of the higher technician in Sports Training at the University of Artemisa, which responds to current demands. The investigative approach is presented as its general strategy. The mode of action. The diagnosis of the initial state is presented which reveals the existence of the research problem. Theoretical, empirical, and statistical methods were used. The results obtained in the indicators of the variable from its practical application and the experts' criteria manifest the feasibility and potential of the Didactic Strategy, evaluating it as very appropriate.